ANALYSIS OF ISLAMIC RELIGIOUS EDUCATION CURRICULUM IN CLASS VI OF ELEMENTARY SCHOOL 07 BENGKULU CITY - Sapruni, Sapruni; Al Fauzan Amin; Rohimin, Rohimin; Suradi, Ahmad; Aprianti, Nefi (Conciencia, 2024)
This study was to determine and examine the "Analysis of Islamic Religious Education Curriculum grade VI at SD Negeri 07 Bengkulu City. This research was conducted using a phenomenological approach. This type of research is qualitative research that looks and listens more closely and in detail to individual explanations and understandings of their experiences. The phenomenological approach is based on the researcher's interest in examining more deeply the phenomena experienced by key informants. The research was conducted at SD Negeri 07 Bengkulu City. The informants in this study were the principal, Islamic Religious Education teacher, and grade VI students. Data collection was conducted using several techniques, namely; (a) observation; (b) interviews; and (c) documentation studies. To ensure the validity of the data, several efforts were made as follows: (a) extending the data collection period, (b) making continuous and careful observations, (c) triangulating, and (d) involving peers to discuss. From the results of the review in this study, it was found that there is an independent curriculum which is a reference in implementing Islamic religious education subjects, which produces students who have noble character, independence, critical reasoning, creativity, mutual cooperation, a sense of diversity in accordance with the objectives of the independent curriculum integrated in Islamic religious education learning.